Responding to mental health needs after terror attacks. (13th August 2019) - Allsopp, Kate; Brewin, Chris R; Barrett, Alan; Williams, Richard; Hind, Daniel; Chitsabesan, Prathiba; French, Paul
Abstract : Serious problems identified after the 2005 London bombings still remain, argue Kate Allsopp and colleagues